Red blood cell storage duration is not associated with clinical outcomes for acute chest syndrome in children with sickle cell disease. Issue 11 (30th May 2015) - Fields, Melanie E.; Hulbert, Monica L.; Chen, Ling; Berlin, Ari N.; Jackups, Ron; Spinella, Philip C.
Abstract : BACKGROUND: Providers commonly transfuse sickle cell disease (SCD) patients with fresh red blood cells (RBCs) as treatment for acute chest syndrome (ACS). The objective of this study was to determine if there is an association between the storage duration of RBCs and length of hospitalization and oxygen requirement after transfusion in pediatric SCD patients with ACS. STUDY DESIGN AND METHODS: This is a retrospective cohort study of pediatric SCD patients with ACS treated with a simple RBC transfusion over 8.5 years at a single institution. Multivariate generalized estimation equation analysis was used to identify associations between storage duration of RBCs and outcome measures. RESULTS: A total of 234 ACS episodes in 131 subjects were included. The median storage duration of the oldest unit of transfused RBCs was 17 days (interquartile range, 11‐26). The majority of ACS episodes, 77.4%, were treated with 1 unit of transfused RBCs; 20.9% received 2 units; and 1.7% received 3 or more units of RBCs. There was no association between the storage duration of the oldest unit of transfused RBCs and either duration of hospitalization or supplemental oxygen requirement after transfusion in multivariate analyses. CONCLUSION: This retrospective study is one of the first to investigate the role of the storage lesion in children with SCD and does not support the preferential transfusion of fresh RBCs for ACS. Ultimately, a randomized controlled trial is necessary to determine whether the storage age of RBCs affects outcomes for patients with SCD and ACS.